EVALUATING THE INFLUENCE OF GREEK GEOPARKS TO THE LOCAL COMMUNITIES - Fassoulas, C.; Zouros, N. (Bulletin of the Geological Society of Greece, 2010)
The European geoparks are new and effective instruments for the interpretation, protection and promotion of geological heritage aiming to a sustainable local development. Since 2000 the two Greek geoparks, the Lesvos Petrified Forest and the Psiloritis Natural Park have developed a great number of activities. Because of their differences, these two geoparks can be used as good examples to evaluate contribution of geoparks to local economy. In Psiloritis geopark operation is supported by the AKOMM –Psiloritis SA Development Company and significant funds have been raised for geo-protection and geo-tourism through European projects, a certain operational budget from local funds has been established and a new action plan has been developed under the forthcoming Leader+ project. In Lesvos Petrified Forest geopark operation is supported by the Natural History Museum of the Lesvos Petrified Forest which is responsible for research activities, protection and promotion of this protected natural monument. Main activities were funded by the North Aegean Regional Operational Framework as well as by INTERREG and LEADER initiatives to promote geoconservation, geotourism and local development. Furthermore, in both areas exchange of know how and best practices assisted local stakeholders and staff of local authorities to develop skills on the nature protection and promotion of geoheritage. Additionally, a great number of publications, environmental education programs and promotional activities contributed to the information and education of local communities, as well as of visitors on their geological and natural heritage. All the above mentioned activities have significant impact in local economy through the development of geotourism.